2019
DOI: 10.1021/acsomega.8b03578
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the In Vivo Antimicrobial Activity of a Self-Assembling Peptide Hydrogel Using a Galleria mellonella Infection Model

Abstract: Technological advances in protein biochemistry now enable researchers to modify the structure of peptides to enable them to possess self-assembling properties, forming hydrogels at low concentrations. Peptides can be altered further to provide multifunctional characteristics, for example, to demonstrate antimicrobial properties. The aim of this article is to investigate the in vivo toxicity and antimicrobial properties of a low molecular weight (naphthalene-2-ly)acetyl-diphenylalanine-dilysine-OH (NapFFKK-OH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…These results do not differ statistically (log-rank Mantel-Cox) from controls treated with PBS or 6% (v/v) DMSO. Peptides that have no toxicity in this model have been demonstrated by several studies [66][67][68]. Another way to study the toxic effects in the G. mellonella model is through histological analysis [69].…”
Section: Toxicity Studiesmentioning
confidence: 85%
“…These results do not differ statistically (log-rank Mantel-Cox) from controls treated with PBS or 6% (v/v) DMSO. Peptides that have no toxicity in this model have been demonstrated by several studies [66][67][68]. Another way to study the toxic effects in the G. mellonella model is through histological analysis [69].…”
Section: Toxicity Studiesmentioning
confidence: 85%
“…[37][38][39] During the past few years, these photoactive materials have also been used in the preparation of the antimicrobial hydro- Figure 5. Low molecular weight hydrogel-forming peptide NapFFKK-OH reported by McCloskey et al [26] Figure 6. Small molecule-based hydrogel reported by Cheng et al [31] gel.…”
Section: Photoactive Antimicrobial Hydrogelmentioning
confidence: 98%
“…It was found that NapFFKK-OH exhibited antimicrobial activity and can be used for the prevention of hospital infections as well as in therapeutic treatment. [26]…”
Section: Peptide-based Antimicrobial Hydrogelmentioning
confidence: 99%
“…Hemolymph clotting, equivalent to mammalian blood clotting, is followed by melanization. The cellular response results in the encapsulation of the infecting pathogen and phagocytosis (McCloskey et al, 2019). When control larvae were infiltrated with saline solution, with E. coli or simply picketed, they were asymptomatic and neither death FIGURE 6 | Melanization in Galleria mellonella larvae infected with strains of B. cenocepacia occurs in the presence of the pathogen and does not depend on the presence of OLs.…”
Section: The Absence Of Ols In B Cenocepacia Reduces Their Virulencementioning
confidence: 99%